ENGLISH PRONUNCIATION PROBLEMS ANALYSIS FACED BY ENGLISH EDUCATION STUDENTS IN THE SECOND SEMESTER AT INDO GLOBAL MANDIRI UNIVERSITY - Muhammad Dzulfiqor Ammar (Universitas Indo Global Mandiri, 2022)
The aims of this research were to determine student’s problems in pronunciation, especially consonants, vowels, and diphthongs. The participants of this study were the second-semester students of the Indo Global Mandiri English Education Study Program. The researcher chose second-semester students because students had understood the phenomenon of pronunciation and they have taken IEC: Pronunciation courses. There were 23 students involved in this research. The data were collected by conducting direct meetings through a performance test that used three forms of tests such as pronounced 44 sentences, pronounced 31 minimal pairs, pronounced one passage with mixed sounds, and their voices made by the students were recorded by mobile phone. The data showed that in fact, most of the students have problems with pronunciations. It is found that the students had problems in pronouncing the English sounds of consonant [v], [θ], [ð], vowel [æ], [ʌ], [ɔ:] and diphthong [eɪ], [oʊ], [аʊ], [aɪ]. Some of the factors that cause pronunciation problems that students face are: the absence of the sound in their mother tongue, students unfamiliar with the targeted words, and students get used to the wrong pronunciation that has been taught before.